Risk Factors for Tuberculosis among Children under Five Years of Age at the Community Lung Health Centre - Rezania, Asyfiradayati; Dyimes, Presidiana Wardhani; Dwi, Linna Suswardany (International Journal of Psychosocial Rehabilitation, 2020)
Children with tuberculosis, especially those younger than five years, are at high risk of death if not treated adequately. Tuberculosis (TB) in children caused an estimated death of around 140.000 every year. This study aimed to analyse the risk factors for TB incidence among under 5-aged children at the Community Lung Health Centre in Surakarta. It was an observational study with the case-control approach by exhausted sampling (46 cases). The cases used in this study were 41 cases due to five samples dropped out. The total samples analysed were 41 cases and 82 controls. The controls were taken from the closest neighbour of the cases. The data were collected via face-to-face interviews with the mother of children that followed a validated-structured questionnaire. Chi-Square test was used to analyse the data, with p-values less than 0.05 considered statistically significant. The samples resided in seven Districts of Surakarta, Sukoharjo, Karanganyar, Boyolali, Sragen, Klaten, and Wonogiri. All the children in the case and control group were BCG vaccinated. Contact tracing prioritising children in low socio-economic households in a TB high-burden setting is not only essential but also feasible. It will contribute to overall case detection.